Multi-Stage Discrete Programming of the Production Line - Robert Bucki; Franciszek Marecki (Communications - Scientific letters of the University of Zilina, 2013)
The paper highlights the problem of multi-stage optimization consisting in determining a timescale of realization orders of objects. Each production stage requires solving a multi-stage discrete programming problem. Production is optimized from the given state of the line to the state in which the line capacity does not allow any further manufacturing. Tools to be replaced in production aggregates are determined by means of heuristic algorithms. Optimization of the manufacturing line is brought to the discrete linear model within each stage.